Identifying organizational variables to the implementation of horizontal strategy in conglomerates. Issue 5 (24th June 2020) - Verma, Pratima; Sharma, R.R.K.; Kumar, Vimal; Hsu, Sung Chi; Lai, Kuei-Kuei
Abstract : Purpose: The paper aims to investigate organizational variables and develop their relationship with horizontal strategy. The cultural dimensions and organization structure have been considered as organizational variables. The study also aims to shed light on the implementation horizontal strategy in conglomerates. Design/methodology/approach: A survey was carried out with 122 conglomerate firms for examination. These companies were chosen to be of different sizes and sectors. The multiple regression analysis was utilized to analyze the data. Findings: The results reveal that conglomerate firms also have a horizontal strategy. Additionally, organizational cultural dimensions namely, collectivism, clan culture, market culture and long-term orientation; formal and informal relationship; and horizontal organization structure (HOS) have positive and significant relationship with horizontal strategy. No significant relationship was found between uncertainty avoidance and adhocracy culture, and horizontal strategy. Research limitations/implications: The major contributions of this study are explicitly identified as horizontal strategy exists in the conglomerate firms where the few organizational variables play a significant role in horizontal strategy implementation. Originality/value: This study has been done in an effort to make supporting guidelines to fill the gaps in conglomerate firms. This study offers an effective role of cultural dimensions and structure as drivers of horizontal strategy implementation, and this study spells out and extends the literature and proposes a conceptual framework.